Role of cuticular genes in the insect antimicrobial immune response - Mallick, Sreeradha; Eleftherianos, Ioannis (Frontiers in Cellular and Infection Microbiology, 2024)
Insects are established models for understanding host-pathogen interactions and innate immune mechanisms. The innate immune system in insects is highly efficient in recognizing and opposing pathogens that cause detrimental effects during infection. The cuticular layer which covers the superficial layer of the insect body participates in host defense and wound healing by inducing innate immune responses. Previous studies have started to address the involvement of cuticular genes in conferring resistance to insect pathogens, particularly those that infect by disrupting the insect cuticle. For example, the cuticular gene Transglutaminase (TG) in Drosophila melanogaster plays a structural role in cuticle formation and blood coagulation and also possesses immune properties against pathogenic infection. However, more information is becoming available about the immune function of other cuticular gene families in insects. In this review, we aim to highlight the recent advances in insect cuticular immunity and address the necessity of pursuing further research to fill the existing gaps in this important field of insect immunology. This information will lead to novel strategies for the efficient management of agricultural insect pests and vectors of plant and human disease.